1990
DOI: 10.1111/j.1365-2044.1990.tb14393.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure measurement during transport A comparison of direct and oscillotonometric readings in critically ill patients

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…Most, but not all, studies assessing this relation have shown that sphygmomanometric techniques and oscillometric devices (including Dinamap) underestimate systolic pressure (range: 6-19%) and overestimate diastolic pressure (range: 5-27%). 6,[8][9][10][11][12][13] Our results confirm that oscillometric techniques underestimate systolic and overestimate diastolic blood pressures to a degree similar to that previously reported, but add to these observations by showing that the magnitude of error is comparable among lean, overweight, class I/II obese, and class III obese subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Most, but not all, studies assessing this relation have shown that sphygmomanometric techniques and oscillometric devices (including Dinamap) underestimate systolic pressure (range: 6-19%) and overestimate diastolic pressure (range: 5-27%). 6,[8][9][10][11][12][13] Our results confirm that oscillometric techniques underestimate systolic and overestimate diastolic blood pressures to a degree similar to that previously reported, but add to these observations by showing that the magnitude of error is comparable among lean, overweight, class I/II obese, and class III obese subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Mean differences for DBP ranged from 8.3 to 18, with SDs from 1.1 to 9.3 mm Hg. 13 Some comparisons of the auscultatory versus oscillometric methods have been good, 14 some poor (especially DBP [15][16][17][18][19] ), some with oscillometric pressures too high, 20 and some too low 21 in a variety of clinical populations. Only a single, early study measured oscillometric arm pressures along with directly recorded aortic pressures and found them comparable.…”
Section: Smulyan Et Al Calculated Aortic Pulses 153mentioning
confidence: 99%
“…The inaccuracy of NIBP has been shown to persist out of hospital as well. A French land-based pre-hospital medical team found 44% of systolic readings results differed by 20% or greater in one group [23], and another intensive care transport team concluded that NIBP underestimated systolic pressure by 13-21%, yet over estimated diastolic by 5-27% [13]. Feasibility studies have suggested that IABP monitoring can be established in the pre-hospital environment [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In a transport environment, it is recommended to have a lower threshold for invasive arterial monitoring [2], as the accuracy of oscillometric NIBP measurement devices is reduced by noise and vibration in the transport environment [13]. Noise and vibration are significant in aircraft [14], and it has been suggested that this may make NIBP measurement less accurate in the aeromedical environment [15].…”
mentioning
confidence: 99%